Attitude towards HPV vaccination among Iranian women living in Malaysia - Minhat, Halimatus Sakdiah; Mustafa, J.; Sarabi, S. (IDOSI Publications, 2013)
Persistent infection with human papillomavirus (HPV) is a prerequisite for the development of cervical cancer. Highly immunogenic HPV vaccines was developed and licensed for the primary prevention of cervical cancer. This study aims to assess the attitude and its associated factors among Iranian women living in Malaysia. A cross-sectional study, using a convenience sampling method was conducted among 271 Iranian women aged 18 to 60 year olds who were living in Malaysia. Data collection was conducted using a self- administered questionnaire. A total of 271 Iranian women had participated in this study, with the mean age of 35.2 years. Majority of the respondents involved were 30 years of age and above (57.9%), single (51.7%), received tertiary education level (82.7%), unemployed (68.6%) and had no income (68.3%), did not have any children (57.9%) and also had positive attitude towards HPV vaccination (79.7%). Education level, income, history of previous genital infection and pap smear were significantly associated with the respondents’ attitude towards HPV vaccination. However, only education level was found to be the significant predicting factor for positive attitude. In view of the positive attitude, they should be made highly accessible to the HPV vaccines. Providing them with an adequate knowledge on the availability and accessibility of the vaccine to their understanding is a necessity.